Dopant‐Free Squaraine‐Based Polymeric Hole‐Transporting Materials with Comprehensive Passivation Effects for Efficient All‐Inorganic Perovskite Solar Cells. (21st October 2019) - Xiao, Qi; Tian, Jingjing; Xue, Qifan; Wang, Jing; Xiong, Bijin; Han, Mengmeng; Li, Zhen; Zhu, Zonglong; Yip, Hin‐Lap; Li, Zhong'an
Abstract: Development of high‐performance dopant‐free hole‐transporting materials (HTMs) with comprehensive passivation effects is highly desirable for all‐inorganic perovskite solar cells (PVSCs). Squaraines (SQs) could be a candidate for dopant‐free HTMs as they are natural passivators for perovskites. One major limitation of SQs is their relatively low hole mobility. Herein we demonstrate that polymerizing SQs into pseudo two dimensional (2D) p–π conjugated polymers could overcome this problem. By rationally using N, N‐diarylanilinosquaraines as the comonomers, the resulting polysquaraine HTMs not only exhibit suitable energy levels and efficient passivation effects, but also achieve very high hole mobility close to 0.01 cm −2  V −1  s −1 . Thus as dopant‐free HTMs for α‐CsPbI2 Br‐based all‐inorganic PVSCs, the best PCE reached is 15.5 %, outperforming those of the doped‐Spiro‐OMeTAD (14.4 %) based control devices and among the best for all‐inorganic PVSCs. Abstract : Quadratur des Kreises : N, N ‐Diarylanilinosquaraine als Comonomere führen zur Bildung von Polysquarain‐Lochtransportmaterialien (HTMs) mit sehr hoher Lochmobilität. Ihr Einsatz als dotandfreies HTM in rein anorganischen α‐CsPbI2 Br‐Perowskitsolarzellen ergibt einen Wirkungsgrad (PCE) von bis zu 15.5 %, einer der besten Werte für rein anorganische PVSCs.